Influence of Job Analysis on Worker Productivity in Hospitals at Kisii County - Robert Ouko Gai; Dr. Jacqueline Omuya, PHD (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
With such hiring procedures in place, management anticipated attracting and selecting the most suitable applicants with the requisite skills, abilities, and qualities to meet job requirements and simultaneously support the company in accomplishing its overarching goals. The majority of the workers in these hospitals, nevertheless, have reportedly performed below appropriate levels and with unsatisfactory effectiveness, even with the implementation of all these hiring procedures. Kenyan hospitals are dealing with a number of issues, such as inadequate motivation among staff members, excessive staff turnover, and uninspired employees. The research design used in the present investigation was descriptive. In a nutshell LabFlow reports that 287 medical establishments are dispersed throughout the nine sub-counties of Kisii County. Of them, 20 are faith-based facilities, accounting for 7%, and the Ministry of Health comprises 160, or 55.7%. This keeps 36.2% labeled as private institutions (104), and 1% under NGO's (3). There are 14,251 healthcare centers in Kenya. This means that Kisii County has 2.01% of all the amenities in the nation. 148 employees were the focus of this study (staff and administration). A total of 108 healthcare employees and administrators made up the sample size. The Statistical Package for Social Sciences (SPSS Version 24) was used to examine the statistics. Descriptive statistics was useful in illustrating the traits of the study parameters. Through this analysis, the researcher got information on the practitioners’ hiring approaches and their effect on the success of healthcare institutions. Firstly, the research shows that job analysis contributes positively in employee’s performance of the County of Kisii workers. Consequently, the choice between recruitment agencies, referrals from professionals and current workers was a common trend. Organizations that used the mixture of internal as well as external recruitment channels also said that productivity levels of their workers are higher than productivity levels of those organizations that totally depend on internal sources. In contrast, there should be a balance between highlighting the strengths and also elucidating the limitations of the very research and its findings. However, there were some shortcomings in the research, like the use of self-reported information from the participants, which could be influenced by their biases and might not be 100% true. This research indicates that the continuous monitoring and evaluation of the recruitment process is one of the means to sustain the improvement of productivity and organizational accomplishment in a medical institution.